Answer:
and
![( -√(29)+3 )/(10)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/p3t20l7jkqssalptm95jjz6adrh2w2bds3.png)
Explanation:
Your equation is
![5x^(2)-3x-1=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/nxi8yt8bmqhd5lqqqk84f9tmf5t4zv9y7l.png)
But you need to put it in quadratic form, which is:
Ignore the Â, I couldn't get rid of it
If a=5, b=-3, and c=-1 then you just fill in the spaces
![x=\frac{-(-3)±\\\sqrt{(-3)^(2)-4(5)(-1) }}{2(5)}](https://img.qammunity.org/2021/formulas/mathematics/middle-school/j73cfo1esr0snmx8x1cidetwff9qqkv70j.png)
Then you simplify the equation
![x=(3±\\√(9-20(-1) ))/(10)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/gfaqfw3xena411zwfby6lsnjtjbc1rmpip.png)
![x=(3±\\√(9+20))/(10)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/zx69uzmvsqweyxxxz3rr69u7nuqh8xlkkb.png)
![x=(3±\\√(29))/(10)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/f13owf4hhgcaptr1echwfgqji63sg331l8.png)
Then you separate the equation
![x=(3+\\√(29))/(10)\\x=(3-\\√(29))/(10)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/knxhsxd87eu6rrli9shdbifio67xw42769.png)
Then you switch the numerators numbers
![x=(-\\√(29)+3)/(10)\\x=(\\√(29)+3)/(10)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/cb03mmy2voo9jjyur2ua47145hkp9qihje.png)
And that is your solution.